Collapse Risks of Fail-Safe RC Frames Due to Earthquakes: Fragility Assessments - Mangkoesoebroto, Sindur P.; Prayoga, Made H.; Parithusta, Rizkita (Journal of Engineering and Technological Sciences, 2019)
The objective of this study was to determine the collapse risk of fail-safe reinforced concrete (RC) frames due to earthquakes by newly developed fragility curves. The curves were constructed based on the collapse mechanism, instead of measures of lateral drift as customarily adopted. The procedure was applied to RC open frames that were seismic resistant. A fail-safe mechanism was imposed by allowing plastic hinges to be formed mainly in the beams. This automatically satisfied the stronger column-weaker beam requirement; shear failure was neither tolerated anywhere in the columns nor in the beams. Two kinds of fail-safe RC frames were investigated: special moment resisting frames (SMF) and ordinary moment resisting frames (OMF). Their earthquake collapse risk was computed and compared. Inelastic time history (NLTH) and the non-linear static procedure (NSP) were conducted to assess their structural performance. The results showed among others that the fail-safe OMF had lower collapse risk than the fail-safe SMF. The collapse prevention performance level in NLTH could only be achieved for the fail-safe frames. The non-linear time history analysis should be the only method used for seismic reevaluation/safety checking of building frame structures.